2010
DOI: 10.3109/08820130903401736
|View full text |Cite
|
Sign up to set email alerts
|

Fas Gene Polymorphisms in Systemic Lupus Erythematosus and Serum Levels of Some Apoptosis-Related Molecules

Abstract: The frequency of the Fas gene polymorphism at positions-1377 G/A and -670 A/G in 249 patients with systemic lupus erythematosus (SLE) and 212 healthy controls were investigated using the allele-specific polymerase chain reaction. On evaluation of genotype and allelic distributions at position -670, no significant difference was observed between patients and controls. At position -1377, the GG genotype and G allele was higher in the patient group than in the control group (p < 0.036). The haplotype frequencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
1
19
1
Order By: Relevance
“…In general, apoptosis induction occurs via 2 classic pathways, extrinsic, and intrinsic. The extrinsic pathway is initiated by the ligation of death receptors (i.e., Fas) in the cell membrane, which results in the conversion of procaspase-8 to its activated form, after which procaspase-3 is activated either directly or by cleavage of Bid (12). In the intrinsic pathway, the 2 main molecules involved in the regulation of apoptosis are Bax that have a pro-apoptotic effect and B-cell lymphoma-2 (Bcl-2), with anti-apoptotic activity (13).…”
Section: Introductionmentioning
confidence: 99%
“…In general, apoptosis induction occurs via 2 classic pathways, extrinsic, and intrinsic. The extrinsic pathway is initiated by the ligation of death receptors (i.e., Fas) in the cell membrane, which results in the conversion of procaspase-8 to its activated form, after which procaspase-3 is activated either directly or by cleavage of Bid (12). In the intrinsic pathway, the 2 main molecules involved in the regulation of apoptosis are Bax that have a pro-apoptotic effect and B-cell lymphoma-2 (Bcl-2), with anti-apoptotic activity (13).…”
Section: Introductionmentioning
confidence: 99%
“…The FAS -670A allele was associated with susceptibility to systemic lupus erythematosus (SLE) in a Japanese population (Kanemitsu et al, 2002). However, contradictory results between populations have been found in several autoimmune diseases (Kanemitsu et al, 2002;Niino et al, 2002;van Veen et al, 2002;Hiraide et al, 2005;Agarwal et al, 2007;Arasteh et al, 2010). A study in Caucasians found no association of the polymorphism with pSS susceptibility; however, the authors did not assess the possible influence of the FAS -670A>G polymorphism on sFas levels (Mullighan et al, 2004).…”
Section: Introductionmentioning
confidence: 78%
“…However, another group of studies in different populations found no such association (Niino et al, 2002;Arasteh et al, 2010). The difference in these association studies may be due to differences in genotype distributions between populations.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations